2020
DOI: 10.1016/j.phro.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of clinical preferences in treatment planning of radiotherapy for prostate cancer using Pareto fronts and clinical grading analysis

Abstract: Introduction: Radiotherapy treatment planning is a multi-criteria problem. Any optimization of the process produces a set of mathematically optimal solutions. These optimal plans are considered mathematically equal, but they differ in terms of the trade-offs involved. Since the various objectives are conflicting, the choice of the best plan for treatment is dependent on the preferences of the radiation oncologists or the medical physicists (decision makers).We defined a clinically relevant area on a prostate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to a recent systematic review and meta-analysis, patients who receive the prostate RT have 21.9% and 31.9% chances of having acute gastrointestinal and genitourinary toxicities, and 16.2% and 28.0% for the late toxicities, respectively [ 42 ]. In our study, the OAR, bladder was not selected as the trade-off criterion according to similar studies on evaluation of MCO function for the prostate RT planning [ 23 , 25 , 39 ]. This arrangement facilitated better illustration of the trade-offs between the PTV and rectum doses on the two-dimensional Pareto surface.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review and meta-analysis, patients who receive the prostate RT have 21.9% and 31.9% chances of having acute gastrointestinal and genitourinary toxicities, and 16.2% and 28.0% for the late toxicities, respectively [ 42 ]. In our study, the OAR, bladder was not selected as the trade-off criterion according to similar studies on evaluation of MCO function for the prostate RT planning [ 23 , 25 , 39 ]. This arrangement facilitated better illustration of the trade-offs between the PTV and rectum doses on the two-dimensional Pareto surface.…”
Section: Discussionmentioning
confidence: 99%
“…Maree et al ( 18 ) showed that their observers judged the treatment plans on "volumes with dose higher than 200%, the activation of dwell positions near the OARs, and the location of areas where the target was not covered" in addition to the DVH parameters. Kyroudi et al ( 16 ) used an observer study to find the optimal part of the Pareto front for EBRT prostate cancer treatments, showing that the observers preferred treatment plans with some PTV under-dosage, since these spared the rectum.…”
Section: Discussionmentioning
confidence: 99%